2017
DOI: 10.3390/soc7030024
|View full text |Cite
|
Sign up to set email alerts
|

How Legacies of Genocide Are Transmitted in the Family Environment: A Qualitative Study of Two Generations in Rwanda

Abstract: Abstract:The 1994 genocide against the Tutsi in Rwanda and its aftermath led to large-scale individual traumatization, disruption of family structures, shifts in gender roles, and tensions in communities, which are all ongoing. Previous research around the world has demonstrated the transgenerational effects of mass violence on individuals, families and communities. In Rwanda, in light of recurrent episodes of violence in the past, attention to the potential 'cycle of violence' is warranted. The assumption tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
15
0
2
Order By: Relevance
“…The 1994 genocide against the Tutsi in Rwanda killed more than a million people in only a short time (Barrow, 2016 ) and has affected nearly all Rwandans, and its effects still occur as one of the factors of a higher rate of mental disorders (Saraceno et al, 2007 ). However, although the government of Rwanda has made efforts to combat with mental disorders associated with this hazardous event through availing financial and human resources for proving mental healthcare services appropriately, the provision of efficient and effective mental health services remains a challenge (Berckmoes et al, 2017 ; Negash et al, 2020 ). Later, preceding studies found a remarkable improvement in providing mental health services due to an increase in financial and human resources and increase in the quality of the services provided (Mutuyimana et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 1994 genocide against the Tutsi in Rwanda killed more than a million people in only a short time (Barrow, 2016 ) and has affected nearly all Rwandans, and its effects still occur as one of the factors of a higher rate of mental disorders (Saraceno et al, 2007 ). However, although the government of Rwanda has made efforts to combat with mental disorders associated with this hazardous event through availing financial and human resources for proving mental healthcare services appropriately, the provision of efficient and effective mental health services remains a challenge (Berckmoes et al, 2017 ; Negash et al, 2020 ). Later, preceding studies found a remarkable improvement in providing mental health services due to an increase in financial and human resources and increase in the quality of the services provided (Mutuyimana et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Според него родителите кои го преживеале холокаустот се разликувале од останатите родители само во однос на промената на улогите родител -дете каде детето поради грижа за родителот ја презема "родителската функција". Истиот наод се потврдува и во истражувањето на Даниели со соработниците (Danieli et al, 2015) и истражувањето на мајките од Руанда спроведено од страна на Беркмос со соработниците (Berckmoes et al, 2017).…”
Section: пренесување на траумите од генерација на генерацијаunclassified
“…Беркмос со соработниците (Berckmoes et al, 2017) интервјуирале мајки кои го преживеале геноцидот во Руанда и нивните деца. Откриле дека мајките не ги споделувале своите искуства со децата и се надевале дека такви настани нема да се случат во иднина.…”
Section: истражувања за пренос на траумите низ генерацииunclassified
“…Numerous surveys have estimated the prevalence of PTSD and other mental disorders, including among children, typically registering high prevalence rates (Dyregrov et al 2000;Kayiteshonga et al 2018;Munyandamutsa et al 2012;Schaal and Elbert 2006). There has been increasing attention to the well-being of the 'second generation' born after 1994, amid concerns of ITT (Berckmoes et al 2017;Rudahindwa et al 2020).…”
Section: Introductionmentioning
confidence: 99%